The molecular logic of early metastasis in pancreatic cancer: crosstalk between tumor and microenvironment - Costamagna, Andrea; Ghiglione, Noemi; Martini, Miriam (Frontiers in Cell and Developmental Biology, 2025)
Pancreatic ductal adenocarcinoma (PDAC) exhibits early systemic dissemination that precedes clinical detection, challenging the classical model of metastasis as a late evolutionary event. Mounting evidence indicates that molecular and cellular programs enabling invasion and distant colonization emerge at preinvasive or early carcinoma stages. This mini-review synthesizes recent advances defining how tumor-intrinsic mechanisms, such as KRAS-driven basal extrusion, epithelial–mesenchymal plasticity and chromosomal instability, cooperate with microenvironmental cues to promote early metastatic competence. The desmoplastic stroma, rich in fibroblasts, inflammatory mediators and aligned extracellular matrix, provides both structural and biochemical support for tumor-cell escape. Additionally, neural and immune interactions, including chemokine and cytokine signaling, facilitate perineural invasion and systemic pre-metastatic niche (PMN) conditioning via extracellular vesicles and cytokine networks. Recognizing PDAC as a systemic disease from inception reframes therapeutic priorities: early systemic therapy and biomarker-guided patient stratification may intercept occult dissemination. We propose that integrating mechanistic insights on tumor–microenvironment crosstalk with perioperative and liquid-biopsy-driven clinical strategies could redefine early intervention in PDAC.